1990
DOI: 10.1093/ndt/5.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload in Haemodialysis Patients Increases the Risk of Bacteraemia: A Prospective Study

Abstract: The incidence of bacteraemia in relation to the degree of transfusional iron overload was studied prospectively in patients from one haemodialysis unit over a 2-year period, with a total follow-up of 181.3 patient-years in 158 patients. Every 3 months, the patients were classified according to the serum ferritin in one of three groups: less than 500, 500-1000 or greater than 1000 micrograms/l. Twenty-nine episodes of bacteraemia were recorded over 181.3 patient-years (yearly incidence of 0.160). The yearly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 0 publications
3
74
1
3
Order By: Relevance
“…Furthermore, iron overload in our patients was due to excessively administered iron rather than hereditary Patients with excessively high serum ferritin levels died from various causes, due to the widespread organ dysfunction caused by iron overload [27,351. Indeed, iron overload has been associated with an increased risk of severe infection [3,12,29,36, 401, cardiovascular disease [34, 391, and malignancy [19, 23, 421. The increased susceptibility to infection, and the increased proliferation of malignant cells in iron overload may be due to depressed phagocytic function of neutrophils and to impaired cell-mediated immunity [30,42,431.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, iron overload in our patients was due to excessively administered iron rather than hereditary Patients with excessively high serum ferritin levels died from various causes, due to the widespread organ dysfunction caused by iron overload [27,351. Indeed, iron overload has been associated with an increased risk of severe infection [3,12,29,36, 401, cardiovascular disease [34, 391, and malignancy [19, 23, 421. The increased susceptibility to infection, and the increased proliferation of malignant cells in iron overload may be due to depressed phagocytic function of neutrophils and to impaired cell-mediated immunity [30,42,431.…”
Section: Discussionmentioning
confidence: 99%
“…Septicaemia with Y. enterocolitica is rare, and it is most often seen in patients who have a predisposing disease, or receiving an iron-chelating therapy, or are in an acute iron-overloaded state (16). Iron has a critical role in bacteria for multiplication in the host, and iron overload impairs the phagocytic activity of neutrophils (6,8,30). Y. enterocolitica strains have the ability to increase their virulence using iron provided in the environment during iron supplementation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, iron-chelating agents and blood transfusions were not administered. Conversely, different studies have reported sepsis caused by Y. enterocolitica in dialyzed patients with mild or high iron overload, iron-chelating treatment or multiple blood transfusions (1,8,12,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodialysis is the 5th most common procedure for patients aged 45 -64 years (1,2). Due to the fact that the procedure of hemodialysis requires prolonged vascular access, patients undergoing chronic hemodialysis are at increased risk of blood-transmitted infections (3). The risk of infection is related to several factors including environmental factors such as contaminated devices, equipment and supplies, environmental surfaces, and personnel's hands (4,5), as well as patient related factors such as the number of years spent on dialysis therapy (dialytic age), partial immunosuppressant, regular hospitalizations, and parenteral interventions frequency (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%